PANORAMIC AITIA IN CHYLOTHORAX - Elilnambi Sundaramoorthy, Kathirvel (South Eastern European Journal of Public Health, 2025)
The etiology of chylothorax can be divided into a)Traumatic b)Spontaneous and c)Idiopathic. Traumatic chylothorax, usually following iatrogenic injury like oesophageal surgery accounts for0.3-5%. Non -iatrogenic traumatic chylothorax are extremely rare (about 31 cases in the last 20 years) so also chylothorax following thyroidectomy (0.5%-6%). Here we present four cases of chylothorax each following a different aetiology for their rarity. Materials and methods: The cases were manged in the department of cardiothoracic surgery. The first case was a 36 yr old man who presented with right sided chylothorax following a road traffic accident. The second case was a 55 yr old woman who presented with left sided chylothorax following thyroidectomy for follicular carcinoma thyroid. The third patient was referred following pericardectomy for constrictive pericarditis with right sided chylothorax and the last case developed bilateral chylothorax following thymectomy for myasthenia gravis. All patients were placed on conservative treatment with tube thorocostomy, low fat diet, medium chain fatty acid diet with parentral nutrition and octreotide for atleast 2 weeks. All patients required surgical intervention with ligation of thoracic duct. The intraop challenge was to identify the leaking duct, which was overcome by instilling a high fat mixture(indigenous), through nasogastric tube soon after induction. Post operative period was uneventful. Results: Operative intervention provides prompt relief for those who fail initial trial of conservative treatment. One should not wait too long before intervening surgically as the waiting period causes malnourishment and metabolic problem s which can interfere with recupertion.